The relationship between the priesthood and the church from the perspective of unity - Petrov, George Daniel (Technium Social Sciences Journal, 2021)
The Church is the extension of the resurrected body of the Son of God in history and in the believers as totality, believers that through baptism and chrismation become her living and active members. The relationship between the sacramental priesthood and the Church can only take place in perfect unity, the Church being absolutely necessary for salvation. Without the historical Church of Christ, namely the laboratory where salvation is being accomplished, humanity would remain subjected to sin and death, unable to know the perfection for which it has been created. Only by getting closer to Christ through the visible hand of the sacramental priesthood in the Church through the Holy Sacraments, the relationship between the Divine and humans acquires a different meaning, and humanity receives a meaning that goes beyond the materiality of the world.